ANALISIS IMPLEMENTASI PENERAPAN STANDAR AKUNTANSI PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN - Khasanah, Uswatun; Nilasari, Ayunda Putri (Transpublika Publisher, 2023)
Financial Report is a form of accountability for state/regional financial management during a period. If the report provided is correct and in accordance with accounting principles, the report can be called qualified. This research was conducted with the aim of reviewing whether government accounting standards have an effect on the resulting financial reports. This research used the literature review method or is called a literature study. This method was carried out by researching, reviewing, describing, and also identifying existing research. The data used in this study was secondary data derived from national scientific articles sourced from Google Scholar. The results of this study indicate that government accounting standards have an effect on the resulting financial reports.